Buprenorphine in pregnant sheep : maternal pharmacokinetics, fetal exposure, and central nervous system distribution - Hakomäki, Henriikka (Publications of the University of Eastern Finland, ISSN 1798-5706, 2023)
Buprenorfiini raskaana olevilla lampailla : emän farmakokinetiikka, sikiöaltistus, sekä keskushermostojakautuminen.
Keywords: Buprenorphine; Pregnancy; Pharmacokinetics; Sheep; buprenorfiini; raskaus; farmakokinetiikka; lammas; buprenorfin; graviditet; farmakokinetik; får